Algorithm 817: P2MESH generic object-oriented interface between 2-D unstructured meshes and FEM - Bertolazzi, Enrico; Manzini, Gianmarco
The software interface P2MESH is a collection of C++ class templates suitable for developing prototypes of high-performance PDE solvers on unstructured 2-D meshes. P2MESH supports several discretization methods on triangles and quadrilaterals, such as finite volume or finite element. The design philosophy of P2MESH does not consider specific model problems or built-in approximation algorithms. The software package is general purpose and it may also be used as a building block in the implementation of numerical codes both for engineering applications and mathematical problems.
Keywords: Finite Element; Finite Volume; Object-Oriented programming; PDE solvers; Unstructured mesh